2003
DOI: 10.1161/01.hyp.0000072820.07472.3b
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Stimulates Monocyte Chemoattractant Protein-1 Production in Vascular Smooth Muscle Cells Via Mitogen-Activated Protein Kinase and Cyclooxygenase-2

Abstract: Abstract-Previous studies have reported that uric acid stimulates vascular smooth muscle cell (VSMC) proliferation in vitro. We hypothesized that uric acid may also have direct proinflammatory effects on VSMCs. Crystal-and endotoxin-free uric acid was found to increase VSMC monocyte chemoattractant protein-1 (MCP-1) expression in a time-and dose-dependent manner, peaking at 24 hours. Increased mRNA and protein expression occurred as early as 3 hours after uric acid incubation and was partially dependent on pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
514
2
9

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 710 publications
(549 citation statements)
references
References 40 publications
16
514
2
9
Order By: Relevance
“…Previous reports have shown that uric acid induces endothelial dysfunction and smooth muscle cell proliferation by activating the RAS and inflammatory mediators such as tumor necrosis factor-alpha and mitogen-activated protein kinases, which are known to induce cardiac hypertrophy [1,10,11,30]. It has been also reported that uric acid in vitro may increase endothelin-1 gene expression in rat cardiac fibroblasts [12].…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have shown that uric acid induces endothelial dysfunction and smooth muscle cell proliferation by activating the RAS and inflammatory mediators such as tumor necrosis factor-alpha and mitogen-activated protein kinases, which are known to induce cardiac hypertrophy [1,10,11,30]. It has been also reported that uric acid in vitro may increase endothelin-1 gene expression in rat cardiac fibroblasts [12].…”
Section: Discussionmentioning
confidence: 97%
“…30 There are multiple ways in which UA can most likely cause vascular remodelling. UA can alter the proliferation and migration of vascular smooth muscle cells 31,32 by activating a series of pathways including mitogen-activated protein kinases, 32,33 platelet-derived growth factors, chemokines (monocyte chemoattractant protein-1), and inflammatory enzymes (COX-2). 32,33 Besides its possible direct effect on vascular smooth muscle cells proliferation and migration, UA may also exert other detrimental effects on the vascular system.…”
Section: Discussionmentioning
confidence: 99%
“…UA can alter the proliferation and migration of vascular smooth muscle cells 31,32 by activating a series of pathways including mitogen-activated protein kinases, 32,33 platelet-derived growth factors, chemokines (monocyte chemoattractant protein-1), and inflammatory enzymes (COX-2). 32,33 Besides its possible direct effect on vascular smooth muscle cells proliferation and migration, UA may also exert other detrimental effects on the vascular system. It is speculated that UA alters the release of endothelial nitric oxide, 34,35 allowing the endothelium to convert from a vasoprotective environment to one that is vasoconstrictive, procoagulant and antifibrinolytic.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Several pathophysiological mechanisms linking SUA to adverse cardiovascular outcome have been proposed, including proliferation of vascular smooth muscle cells, 6 prothrombotic effects mediated by platelet activation, 7 impaired nitric oxide generation and endothelial dysfunction, 8 activation of local renin-angiotensin-aldosterone system 9 and stimulation of inflammatory pathways. 10 Inflammation seems to have a pivotal role in the pathogenesis of hypertension and hypertensive target organ damage. In these lines, we have recently shown that high-sensitivity CRP (hs-CRP) is associated with microalbuminuria, 11 whereas increased hs-CRP and decreased adiponectin levels go together with a state of increased aortic stiffness in hypertensives.…”
Section: Introductionmentioning
confidence: 99%